A randomized open-labeled study to examine the effects of creatine monohydrate and combined training on jump and scoring performance in young basketball players - Salvador Vargas-Molina; Manuel García-Sillero; Richard B. Kreider; Enrique Salinas; Jorge L. Petro; Javier Benítez-Porres; Diego A. Bonilla (Taylor & Francis Group, 2022)
Background Creatine monohydrate (CrM) supplementation has been shown to be an effective and safe nutritional supplement to improve performance; however, the impact of CrM supplementation in young basketball players is less clear. This study evaluated the effects of CrM supplementation during a strength and conditioning training (SCT) program on lower-limb strength parameters and performance in under-16 (U16) basketball players. Methods Twenty-three male U16 basketball players participated in this study (14.3 ± 0.4 years; BMI: 20.7 ± 2.2 kg∙m−2). The players were randomly assigned to either a CrM group (n = 12) that ingested 0.1 g·kg−1·day−1 of CrM or to a non-supplemented control group (n = 11, CON). The athletes participated in an 8-week SCT program consisting of two lower-limb resistance-training sessions and two plyometric sessions per week. Squat jump (SJ), drop jump (DP), countermovement jump (CMJ), and Abalakov (ABK) jump power tests as well as basketball performance (points and minutes per game) were measured before, during and/or after the intervention. Data were analyzed using a general linear model with repeated measures with independent Student's t-test pairwise comparisons. Results The results (95% confidence interval for mean change from baseline) show that there were significant differences for all variables for CrM and CON, respectively: SJ (cm): 2.6 - 6.4, P < 0.01 and 2.2-5.1 P < 0.01; DJ (cm): 2.5-5.6, P < 0.01, and 1.8-4.4, P < 0.01; CMJ (cm): 0.3-0.8, P < 0.01, and 0.2-0.5, P < 0.01; ABK (cm): 2.8-5.5, P < 0.01 and 0.7-2.6, P = 0.003. A significant group x time interaction (p = 0.003, ηp2 = 0.342) was observed in ABK performance. No significant group x time effects were seen in squat jump (p = 0.449, ηp2 = 0.028), drop jump (p = 0.143, ηp2 = 0.099), or counter movement jump (p = 0.304, ηp2 = 0.05). A significant interaction effect was also observed in points per game (p = 0.049, ηp2 = 0.149), while a non-significant but medium effect was seen in minutes per game (p = 0.166, ηp2 = 0.094). Conclusions CrM supplementation in conjunction with resistance and plyometric training increased the lower-limb ABK power and scoring performance in U16 basketball players.